RELIGION, HUMAN RIGHTS AND THE CHALLENGES OF FREEDOM - Nee Karibi, Rhoda Asikia Ige (SCAD Independent, 2015)
All over the world, Religion holds a primal place. Every man is said to believe in a ?god?. Ordinarily there should be no feud in matter of religion, because religion is a personal decision. However, in recent times religion has become an issue and many crimes are committed on the basis of faith. In the 21st century with the promotion of human rights, this ought not to be so. We must note that religion has always been a thorny issue, not with the Christian crusades and the Islamic Jihads. We believe times have changed and each individual should be able to practice his faith without necessarily the follow his fellow. With this at the back of our mind we seek to examine religion, human rights and the challenge of freedom by offering some proposals towards religious harmony in the 21st century.